BUDAYA MARITIM ORANG BUGIS MAKASSAR DAN ARAH TRANSFORMASINYA - Muhammad Akhmar, Andi; Rahman, Fathu; Yunus, Hidayatullah (Universitas Hasanuddin, 2024)
This research discusses the transformation of knowledge and maritime culture of the Makassar Bugis people in South Sulawesi which is caused by developments in science, technology, and socio-economic transformation. The method used in this research is qualitative research, with analysis looking at the relationship between the main aspects of the transformation that occurred in the maritime knowledge and culture of the Makassar Bugis people. The research results show that maritime transformation is occurring rapidly at present, marked by a shift in boat propulsion and navigation technology from traditional to modern. Structural transformation in maritime culture refers to significant changes in the social, economic, and cultural structures in maritime communities. Factors such as globalization, technological modernization, and economic changes are driving this transformation.The transformation of maritime culture influences traditional values ​​and practices, while access to modern knowledge enriches the way society interacts with the sea and maritime resources.